2021
DOI: 10.1177/02646196211019066
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of orientation and mobility training on the quality of life for students who are blind in Iran

Abstract: Orientation and mobility (O&M) training is a practical and helpful method to prepare people who are blind for independent living. Hence, this study aimed to survey the effect of O&M training on the quality of life in students who are blind in Iran. This research was a quasi-randomized controlled trial design. Participants were 24 third-grade to sixth-grade students from two schools for blind in Isfahan, Iran. Using cluster sampling method, one school was assigned to the experimental group ( n = 12) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…As such, blind and visually impaired people may not want to go out and are afraid of being laughed at after falling. These conditions can be ascribed to a lack of orientation and mobility training [ 70 ] or unfriendly environmental conditions (pedestrian obstacles, a lack of warning sounds, etc.). Kuriakose et al [ 71 ] found that using technological aids increases the possibility of employment for visually impaired people.…”
Section: Discussionmentioning
confidence: 99%
“…As such, blind and visually impaired people may not want to go out and are afraid of being laughed at after falling. These conditions can be ascribed to a lack of orientation and mobility training [ 70 ] or unfriendly environmental conditions (pedestrian obstacles, a lack of warning sounds, etc.). Kuriakose et al [ 71 ] found that using technological aids increases the possibility of employment for visually impaired people.…”
Section: Discussionmentioning
confidence: 99%
“…Orientasi dan mobilitas (O&M) mengacu pada kemampuan untuk mengetahui posisi seseorang dalam berhubungan dengan individu lain dan kemampuan bergerak melalui lingkungan. Keterampilan mobilitas pada tunantera umumnya bervariasi (Kamali & Ashori, 2021). O&M juga dipahami sebagai keterampilan yang digunakan untuk mengetahui posisi seseorang di lingkungan serta kemampuan untuk bergerak secara mandiri dan aman (Malik, 2018).…”
Section: Pendahuluanunclassified